Gleicher Lohn für gleiche Arbeit? Zum Zusammenhang zwischen Gewerkschaftsmitgliedschaft und Lohnstruktur in Westdeutschland 1985-1997 - Bernd Fitzenberger; Karsten Kohn (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– This paper examines the relationship between the net union density, as a measure of union power, and the wage structure within and between segments of the German labour market in the period 1985-1997 on the basis of the IAB employment sample. Individual probabilities of trade union membership predicted in estimates by Beck and Fitzenberger (2004) are added to the data set. In accordance with an insurance motive for union membership, ceteris paribus a higher union density is accompanied by a lower wage level and a reduction in residual wage dispersion. In addition to this, qualification-related wage differentials are also smaller in segments with strong unions. In accordance with the minimum-wage character of union-negotiated wages, the compression of the wage distribution occurs in particular in the lower range. The trade union effects also vary with the age of the workers and over time.
Keywords: J51; J31; 330; Gewerkschaftszugehörigkeit; Gewerkschaftspolitik; Lohnstruktur; Lohnfindung; Lohnunterschied; Lohnhöhe; Tariflohn; IAB-Beschäftigtenstichprobe; Westdeutschland; Bundesrepublik Deutschland